Autologous intrauterine platelet-rich plasma instillation for suboptimal endometrium in frozen embryo transfer cycles: A pilot study - Sunita R Tandulwadkar; Manasi V Naralkar; Akash D Surana; M Selvakarthick; Avinash H Kharat (Wolters Kluwer Medknow Publications, 2017)
Introduction: This pilot study was to evaluate the effectiveness of intrauterine infusion of autologous platelet-rich plasma (PRP) in infertile women undergoing frozen embryo transfer cycles with suboptimal endometrium. Material and Methods: Intrauterine instillation of autologous PRP was done in 68 women between 22 and 40 years, over 8 months, with suboptimal endometrial growth, and patients with repeated cycle cancellations, in addition to Estradiol valerate. Frozen embryo transfer was performed when the endometrium reached an optimal pattern in terms of thickness, appearance, and vascularity. Results: The mean pre-PRP endometrial thickness (ET) was 5 mm which significantly increased to 7.22 mm post-PRP. There was a significant increase in vascularity, seen by the number of vascular signals seen on Power Doppler, reaching the zones 3 and 4 of the endometrium. The positive beta Human Chorionic Gonadotropin (hCG) rate was 60.93% and the clinical pregnancy rate was 45.31%. A total of 13 women are in the second trimester, 13 are in the first trimester with a healthy intrauterine pregnancy, one patient had an ectopic gestation, three had blighted ova, two had missed abortions, and two biochemical pregnancies. Conclusion: This study suggests that the use of autologous PRP holds promise in the treatment of women with suboptimal ET and vascularity for embryo transfer. It would help to reduce the incidence of cycle cancellations and thus even help reduce the financial and psychological burden of repeated cancelled cycles.